Peran Pemuda Majelis Pemberdayaan Masyarakat dalam Pendampingan Komunitas Pemulung di Tempat Pembuangan Sampah Terpadu - Muhammad Rifa'at Adiakarti Farid (Islamic Management and Empowerment Journal, 2019)
AbstractThe purpose of this study is (1) To find out the problems faced by the Community Empowerment Council (MPM) in carrying out community empowerment programs in TPST Piyungan. (2) Knowing the impact of community empowerment programs conducted by MPM in TPST Piyungan (3) Knowing the role and participation of youth in community empowerment programs carried out by MPM at TPST Piyungan. This research uses descriptive qualitative method. The results showed (1) Problems faced by MPM came from the surrounding community who did not know the empowerment program in detail (2) Impacts that occurred in the community were united in a community that had been scattered in several collectors groups and better understood their potential (3) Youth who are members of the community empowerment facilitator play an active role in conducting empowerment programs.